Physicians and surgeons formation from the XVI through XIX centuries: The Medicine and Surgery Practical Schools in Peru - Rabí, Miguel (2006)
This document presents a complete study on the Practical Schools of Medicine and Surgery in Lima and some other important Vice Royalty cities. It covers the historical and social evolution from the XVI through the XVIII centuries, and the period before the establishment of the San Fernando College of Medicine and Surgery in 1808. The most important American creole doctors and surgeons graduating from these Practical Schools are mentioned as well as their contribution to medical science and research in public health is also described.